"In‐Out‐In" Percutaneous Reduction Technique for Treatment of Valgus‐Impacted Femoral Neck Fractures: A Technical Trick and Case Series. Issue 1 (23rd November 2022) - Yu, Tianming; Liu, Jianlei; Ying, Jichong; Zhuang, Yunqiang
Abstract : Objective: Valgus‐impacted femoral neck fractures with or without posterior tilt of the femoral head are very common and full of pitfalls in clinical practice, which may lead to femoral neck shortening (FNS) and avascular necrosis (AVN). The study tries to introduce a novel technical trick aiming at anatomical reduction of valgus‐impacted femoral neck fracture with minimally invasive procedure, and summarize the clinical prognosis in case series. Methods: In this retrospective study, 24 patients (seven men and 17 women) with valgus‐impacted femoral neck fractures between May 2017 and July 2020 were managed by "in‐out‐in" percutaneous reduction technique (percutaneous reduction group). Another 24 cases (10 men and 14 women) suffering the fractures underwent in situ fixation were enrolled as control group for function comparison ( in situ fixation group). All patients were followed up for 24–42 months. The clinical outcomes included complications after operations ( χ 2 test) and Harris Hip Score (HHS) for hip function (unpaired t test) in the two groups. The radiographic outcomes were evaluated by collodiaphyseal angle, posterior tilt angle, and FNS before the operation and during the follow‐up in the percutaneous reduction group (unpaired t test). Results: Patients' preoperative data, including age, sex, affected side, fracture types, and medical history, were similar between the two groups, respectively ( p > 0.05). After surgery, the mean HHS at 6, 12, and 24 months were all better in the percutaneous reduction group (76 ± 6.72, 85.34 ± 6.33 and 90.54 ± 5.81) than that in the in situ fixation group (70.86 ± 6.91, 80 ± 6.11 and 84.1 ± 7.82), respectively ( p < 0.05). One patient suffered fixation failure with screws retreat and one patient suffered AVN in the percutaneous reduction group. In the in situ fixation group, AVN occurred in two patients at last follow‐up. There was no significant difference in complication amounts between the two groups ( p > 0.05). In the percutaneous reduction group, collodiaphyseal angle, posterior tilt angle, and amount of FNS were significantly different between preoperative cases and immediately postoperative cases ( p < 0.05). However, there was no statistical difference of the measurements among postoperative cases at different time points (within 24 h, 6 months, and 2 years postoperatively) ( p > 0.05). Conclusions: Our experience of the technique and the case series show that "in‐out‐in" percutaneous reduction technique for treatment of valgus‐impacted femoral neck fracture with or without posterior tilt of the femoral head is safe and effective for achieving successful bone union and satisfactory function. Abstract : "In‐out‐in" percutaneous reduction technique for treatment of valgus‐impacted femoral neck fracture with or without posterior tilt of the femoral head is safe and effective. In our case series, the technique achieved successful bone union and satisfactory function.